The impact of prolonged blockade of the releasing hormone on alterations in cardiac macrophage polarisation subsequent to quercetin administration in rats - T.A. Voroshylova; V.I. Shepitko; Ye.V. Stetsuk; N.V. Boruta; O.V. Vilkhova; M.V. Rud; G.S. Puzyryov; O.V. Sych; А.A. Miahkokhlib (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Cardiomyocytes represent the contractile units of the myocardium, while the maintenance and renewal of the extracellular matrix is a function of fibroblasts. The extracellular matrix provides structural support and mechanical signals for resident cells, and stores biologically active signaling molecules. All cells are subject to changes under the influence of various factors, some of which are induced by macrophages containing CD68 and CD163. The heart is unique in its structure and function, yet it is subject to changes under the influence of various factors. Testosterone plays an important role in the intracellular homeostasis of the heart. Quercetin is an organic substance belonging to the flavonoid family with a wide range of medicinal properties. The purpose of our study was to ascertain the impact of testosterone suppression on immunocompetent heart cells in male rats. The study employed a series of experimental periods, with the introduction of triptorelin and quercetin at varying stages. Materials and methods. The study was conducted on 60 sexually mature male rats. The animals were divided into two groups: control (n = 10) and experimental (n = 50). Animals in the experimental group were injected with a solution of triptorelin at a dose of 0.3 mg of active substance per 1 kg of animal weight to modulate central deprivation of luteinising hormone synthesis. We used primary antibodies against CD163 and CD68. Results. The analysis of the count of monocyte-macrophage cells with CD68 receptors after triptorelin administration showed a sharp increase in their number at 1 month of observation. At 3 months, a significant decrease in this indicator was noted in comparison with the previous study period and with the control group. At month 6, a sharp increase in the number of cells with CD68 receptors was detected. At the 9th month of observation, a decrease in the number of monocyte-macrophage cells was noted compared to the control group. At 12 months, the index was significantly lower than in the previous period. Conclusions. The administration of triptorelin causes quantitative and qualitative changes in the population of macrophages in the interstitial space of the heart. The addition of quercetin changes the ratio in macrophage subpopulations, which may serve to develop effective treatments.